1973
DOI: 10.1073/pnas.70.12.3566
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synthesis of RNA That Contains Polyadenylate by Virion-Associated RNA Polymerase of Vesicular Stomatitis Virus

Abstract: The RNA synthesized in vitro by the virion-associated RNA-instrueted RNA polymerase of purified vesicular stomatitis virus contains polyadenylate sequences. These have been demonstrated by their partial resistance to pancreatic and T, ribonucleases and their capacity to bind to poly(U) filters and oligo(dT)-cellulose. The polyadenylate sequences range in apparent size from 50 to 200 bases, similar to the size of the poly(A) in mRNA from vesicular stomatitis virus-infected cells. Possible mechanisms of polyaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…BHK-21 clone 13 (C1.13) and Vero cells (Flow Laboratories) were grown as monolayers in Dulbecco's modified and F15-modified minimal essential media respectively; BHK-21 C1.13 cells modified for suspension culture (Banerjee & Rhodes, 1973) were grown in Joklik's modified minimal essential medium. All media were supplemented with 5 ~ heat-inactivated calf serum and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…BHK-21 clone 13 (C1.13) and Vero cells (Flow Laboratories) were grown as monolayers in Dulbecco's modified and F15-modified minimal essential media respectively; BHK-21 C1.13 cells modified for suspension culture (Banerjee & Rhodes, 1973) were grown in Joklik's modified minimal essential medium. All media were supplemented with 5 ~ heat-inactivated calf serum and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work in this laboratory (19) has shown that RNA species of two size classes, 31 S and 12-18 S, can be synthesized in vitro by the virion-associated RNA polymerase of VSV. The in vitro RNA products, similar in size to those found in vivo (10), are complementary to the genome and contain poly(A) segments (19)(20)(21), indicating that they could serve as messengers for the VSV proteins. In this report we show that the in vitro 12-18S RNA can be translated in cell-free extracts of wheat germ into proteins which seem identical to the viral polypeptides.…”
mentioning
confidence: 95%
“…[35S]methionine (20 ,Ci/ml) was added at 4 hr after infection. Five minutes after the addition of the label, a 100-fold excess of unlabeled methionine was added and the cell lysate was prepared (23 (25) following the methods of Laemmli (26), and electrophoresed at 125 V for 4 hr.…”
Section: Purification Of Virus and Preparation Of Lysates Of Infectedmentioning
confidence: 99%
“…The RNP complex comprises a genomic RNA encapsidated by a nucleocapsid protein oligomer (N-RNA), associated with the RNA-dependent RNA polymerase (RdRP) consisting of a complex of the large polymerase protein (L) and a phosphoprotein (P) (1)(2)(3). The template RNA is buried between the N-and C-terminal lobes of each N protomer; nevertheless, the overall integrity of the N-RNA structure is maintained during copying by the RdRP (4,5).…”
mentioning
confidence: 99%